*Deformación y cambios en esencia al “Cántico de las criaturas” de san Francisco de Asís en la versión de Ezra Pound - Naranjo Boza, Nicolás (Íkala, Revista de Lenguaje y Cultura, 2006)
This is a detailed commentary and criticism of Ezra Pound's English version of Saint Francis of Assisi's The Canticle of the Creatures. The ideas behind Ezra Pound's version are approached, as well as the context of the original religious poem. Charts are used to collate the metrics of the original and those of the version to prove that Ezra Pound altered and drastically affected the poem's form and content. Received: 27-01-06 / Accepted: 18-06-06 How to reference this article: Naranjo Boza. N. (2006). Deformación y cambios en esencia al “Cántico de las criaturas” de san Francisco de Asís en la versión de Ezra Pound. Íkala. 11(1), pp. 33 – 72